Fracture Classifications in Clinical Practice 2nd Edition - Mostofi, Seyed Behrooz; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
Residents and junior doctors on rotation are under constant pressure to have accurate and up-to-date information available to them. This is never more important than when on rotation in the Emergency Room. Junior doctors often lack experience in orthopaedics making the recognition and accurate identification of fractures and their treatment a challenging task. The second edition of this comprehensive handbook contains a wealth of illustrations and explanatory text, which is organized into a concise repository of information on fractures according to the most widely used classification systems. The classification systems covered include AO and OTA systems. This allows readers the opportunity to make a correct diagnosis using the appropriate criteria, while simplifying the planning of further management and ensuring that communication with experienced staff is more effective.
Keywords: Medicine; Orthopedics; Orthopedic surgery; Medicine & Public Health; Orthopedics; Conservative Orthopedics; Surgical Orthopedics